Renal Trauma: Case Reports and Overview - Campbell D. Tait; B. K. Somani (Case Reports in Urology)
Introduction. Renal trauma patients are largely managed conservatively but on occasion have to be embolised or taken to theatre for definitive surgical management, usually in the form of emergency nephrectomy. Review. We present an overview of renal trauma as illustrated by three interesting cases of blunt renal trauma who presented in quick succession of each other to the Emergency Department. The first case—a 48-year-old-female passenger in a road traffic accident—was treated with life-saving emergency nephrectomy. The second patient—a 47-year-old man who sustained a high impact injury whilst sledging—was managed conservatively on HDU and subsequently on the urology ward. The third patient—an 18-year-old man involved in a road traffic accident—underwent selective embolisation of a pseudoaneurysm after conservative therapy. Discussion. This case series illustrates the surgical, radiological, and conservative approaches to the management of significant renal trauma, which is potentially life threatening.